Implementasi Kebijakan Pembatasan Kendaraan Bermotor Dengan Sistem Ganjil Genap Di Kota Administrasi Jakarta Selatan - Utomo, Ragil Cahyo; Madjid, Udaya; Rusfiana, Yudi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
The aim of this research is to find out how it is implemented, the supporting and inhibiting factors, as well as the efforts made to overcome obstacles to the implementation of the odd-even system of motor vehicle restriction policies in the Administrative City of South Jakarta. As for the focus of implementing the policy of restricting motorized vehicles with an odd-even system in the Administrative City of South Jakarta, this research refers to the opinion of Merilee S. Grindle who states that the success of implementation is influenced by two large variables, namely the content of the policy and the implementation environment. This research uses a qualitative descriptive research method with a post-positivist research paradigm. In this research, there were 7 informants interviewed, consisting of 3 key informants and 4 informants. The data analysis techniques used are data reduction, data presentation, drawing conclusions and verification. The results of this research show: (1) The implementation of the policy of restricting motorized vehicles with an odd-even system in the South Jakarta Administrative City has generally gone well, which can be seen from the decrease in vehicle volume on protocol roads, faster travel times, and increase in passengers on the TransJakarta transportation mode. With this policy, the DKI Jakarta Provincial Transportation Service has succeeded in achieving its goal of increasing the number of people using public transportation. Even though this implementation is not yet completely effective, both the government and society can feel positive changes. (2) Factors that influence the implementation of the odd-even motor vehicle restriction policy in the South Jakarta Administrative City, namely the response of implementing agencies, the attitude of implementing officers, community participation or awareness, availability of human resources, availability of funding sources, activity infrastructure, and weather conditions. (3) Efforts that need to be made to overcome obstacles to the implementation of the policy of restricting motorized vehicles using an odd-even system in the Administrative City of South Jakarta, include the need to improve the quality and facilities of public transportation modes, reviving plans for a paid road policy or Electronic Road Pricing (ERP), increasing coordination and communication between policy implementers, as well as providing stricter sanctions for policy violators to create a deterrent effect.